Etika Kecerdasan Buatan dalam Perspektif Teologi Kristen: Implikasi bagi Pendidikan Agama di Era Society 5.0 : (Studi pada Mahasiswa Teologi) - Tri Subekti; Pujiwati Pujiwati; Indriati Tjipto Purnomo (Jurnal Riset Rumpun Agama dan Filsafat, 2026)
This study examines the use of generative artificial intelligence (GenAI) among theology students and its ethical and theological implications for theological education in the Society 5.0 era. Employing a light mixed-methods sequential explanatory design, the research involved theology students through surveys and semi-structured interviews. The findings indicate that GenAI is primarily utilized as a learning support tool for understanding course materials and developing academic assignments. While students demonstrate awareness of potential bias and ethical concerns, consistent transparency and critical reflection in AI usage remain limited. The theological concept of imago Dei emerges as a significant analytical lens, emphasizing human dignity and moral responsibility in academic practices. The study concludes that GenAI can constructively support theological education when integrated with faith-based ethical literacy and clear institutional guidelines.